Educação para o desenvolvimento sustentável: práticas de educação ambiental no ensino público fundamental das escolas de Fortaleza-CE. - Chaves, Rebeca Gomes (2017)
The study discussed the development of environmental education in the public educational network of the city of Fortaleza, Ceará. In order to do so, the research entered into plural methodological prisms to understand the training of teachers and managers of these schools, as well as the content taught in classrooms. It is important for students to be aware of environmental problems and ways of solving them. The ecological learning received at school also benefits the parents of students who develop reflective behavior on the importance of sustainable development. The objective of this work was to carry out a situational diagnosis of conceptions, practices and difficulties encountered by educators and managers in the promotion of formal environmental education in municipal public education. The study analyzed the public elementary schools, where the political pedagogical projects were verified, as well as records of environmental education activities developed. The interviews were conducted through questionnaires addressed to managers and teachers, with the purpose of knowing the ways of updating these professionals on the subject and the transfer of this knowledge in the classroom. According to the studies carried out, it was observed that, although environmental education is much discussed, there are few projects being developed specifically on the subject. The methodological course included bibliographical research and structured interviews. The sample comprised the participation of professionals from municipal public schools. It is concluded with this study that the active participation of the schools is fundamental for the formation of knowledge and the human conscience on the importance of the dissemination of environmental education. In this chant, the school assumes a challenging role of forming new citizens aware of their role in the world and respect for nature.